Development Of An Algorithm To Reduce The Topographical Effects In Reflected Radiance - Yeap, Eng Choo (2020)
Topographic effects in satellite images are not errors but distortions caused by the solar and surface geometry. Surfaces facing towards the Sun tend to be brighter while surfaces facing away from the Sun are generally darker. This effect is strongly related to solar surface incident angle, and it is one of the main factors that increase spectral variation in satellite images. Spectral variation may reduce accuracy, such as non-supervised classification, which can limit the capability of autonomous remote sensing applications. Many researchers have tried to reduce the effect of topography in the past with success; however, most of these methods are complicated and require many parameters. To address this problem, we developed algorithms that quantify, reduce, and induce topographical effects in satellite images by exploring the relationship between direct and diffuse solar irradiance. These algorithms use data from extraterrestrial irradiance, atmospheric profiles, digital elevation models, and radiative transfer models to calculate the amount of irradiance on Earth’s surface to reduce distortions due to the topographic effect. The algorithm was tested on 11 Landsat 8 OLI satellite images assessed with 120 sample points each. The results demonstrate that this approach suppresses the topographic effect and improves spectral signatures and similarities between satellite images taken on different dates using topographic induction.